1998
DOI: 10.1097/00000421-199802000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and Vinorelbine in the Treatment of Advanced Non-Small-Cell Lung Cancer

Abstract: The aim of this study was to identify a chemotherapy combination that would be active and well tolerated for palliative treatment of advanced non-small-cell lung cancer (NSCLC). From February 1992 to December 1994, a total of 77 patients affected by stage-IIIB and stage-IV NSCLC were treated with carboplatin 350 mg/m2 on day 1 and vinorelbine 25 mg/m2 on days 1 and 8 of each cycle, with cycles repeated every 28 days. All patients were evaluable for response and toxicity. A total of 24 patients showed a partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…At the time this study was planned, single-drug efficacy of vinorelbine had been demonstrated (Gridelli et al, 1997) and the combination of carboplatin and vinorelbine was well tolerated in phase II trials (Masotti et al, 1995;Pronzato et al, 1996;Gridelli et al, 1998Gridelli et al, , 1999Santomaggio et al, 1998). Later vinorelbine/ cisplatin regimens have shown similar efficacy when compared to other cisplatin combinations with third-generation cytotoxic drugs (Schiller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…At the time this study was planned, single-drug efficacy of vinorelbine had been demonstrated (Gridelli et al, 1997) and the combination of carboplatin and vinorelbine was well tolerated in phase II trials (Masotti et al, 1995;Pronzato et al, 1996;Gridelli et al, 1998Gridelli et al, , 1999Santomaggio et al, 1998). Later vinorelbine/ cisplatin regimens have shown similar efficacy when compared to other cisplatin combinations with third-generation cytotoxic drugs (Schiller et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…At top doses 19% of patients had grade III-IV neutropenia (Colleoni et al, 1996). The response-rate for this combination is encouraging, in one phase II study 77 patients with stage III and IV NSCLC received carboplatin 350 mg m -2 D1 and navelbine 25 mg m -2 D1 and D8 q28: response-rate was 31% with no grade IV toxicity observed (Santamaggio et al, 1996).…”
Section: Vinorelbine In Combination Chemotherapy In Nsclcmentioning
confidence: 99%
“…Overview of trials combining carboplatin and vinorelbine in non-small cell lung cancer [6][7][8][9][10][11][12][13] …”
Section: Study N Of Patients Treatment Response Rate Survivalmentioning
confidence: 99%
“…For example, Garst et al, in a study of 42 patients administered carboplatin to an area under the concentration time curve (AUC) of 7 plus vinorelbine at 30 mg/m 2 with G-CSF support, reported a one-year survival rate of 41% ( [9]. Using the same doses, the median survival was 9.5 months in 77 patients treated by Santomagio et al [12]. The response rates in these three studies ranged from 16% to 31%.…”
Section: Introductionmentioning
confidence: 99%